Expert feedback on weights survey results in the Decision Support Tool framework for Optimizing the Water-Energy-Food-Ecosystem Nexus within the Aral Sea Basin - Umarova, Shakhzoda; Verbist, Joren; Gunnink, Marthe; Sadullaev, Ulugbek; Nurbekova, Ruhangiz; Akramkhanov, Akmal (2024)
The present report was developed to describe the main futures of the validation workshop on the Decision Support Tool (DST) organized on the 1st of August in Tashkent, Uzbekistan. The introduction part of the report highlights the Nexus Gains initiative, the initiative's output - Decision Support Tool for optimizing the Water-Energy-Food-Ecosystem Nexus within the Aral Sea Basin, and the workshop aim and objectives, The main part of the report highlights workshop participants, conducted survey within WEFE sector stakeholders, ICARDA's DST instrument and discussions and recommendations during the workshop. The report ends with workshop agenda and list of participants.